Evaluation of rice (Oryza sativa L.) genotypes grown under combined salinity and submergence stresses based on vegetative stage phenotyping - Kaniz, Fatema; Md., Rasel; Islam, Mirza Mofazzal; Begum, Shamsun Nahar; Azam, Md. Golam; Hossain, Mohammad Anwar; Hassan, Lutful (Acta Biologica Szegediensis, 2022)
Sixteen rice genotypes were screened against combined salinity and submergence stresses to find out potential salt-submergence tolerant genotypes. Rice seedlings were subjected to submergence stress including two salinity levels viz., EC-6 dSm-1 and EC-8 dSm-1 for 10 days. Imposition of combined stress considerably decreased the growth parameters in rice seedlings, however ACM-18, ACM-35, and RC-251 demonstrated the maximum value for growth attributes such as leaf live (%), root and shoot length, plant fresh and dry biomass. The results of correlation and regression revealed a significant and negative association of leaf lives (%), root length, fresh weight of root and shoot, and root dry weight with mean tolerance score under combined stress indicating their importance as the useful descriptors for the selection. Euclidean clustering was categorized the rice genotypes into three major clusters, i.e., A-susceptible, B-tolerant and moderately tolerant, and C-highly tolerant. Results of cluster analysis showed that the highly tolerant genotypes namely ACM-18, ACM-35, and RC-251 were placed in the same cluster. Similar results were further confirmed by principal component analysis having the highly tolerant genotypes in the same group. Combining the morphological and multivariate analysis, ACM-18, ACM-35, and RC-251 were selected as promising genotypes for developing high-yielding salt-submergence tolerant rice.